Modern glucose-lowering drugs in liver transplant recipients: improvement in weight, glycemic control, and potentially allograft steatosis - Atthota, Srilakshmi; Joyal, Kayla; Cote, Mariesa; Scalzo, Riley; Singh, Ruby; Consul, Nikita; Kilcoyne, Aoife; Bethea, Emily D.; Dageforde, Leigh Anne (Frontiers in Transplantation, 2023)
Introduction: Recurrent allograft steatosis occurs in one-third of transplanted livers. Antidiabetic agents like glucagon-like peptide-1 receptor agonists (GLP1RA) and sodium-glucose cotransporter type-2 (SGLT2) inhibitors are effective in the management of obesity and hepatic steatosis in the general population; however, there is limited evidence supporting their use in allograft steatosis. We aimed to evaluate their effects on steatosis, body weight, and glycemic control in liver transplant recipients at our institution.In this single-center retrospective cohort study of liver transplant recipients currently on a GLP1RA or SGLT2 inhibitor (transplanted 2015-2022), we compared clinical and radiological data before medication use and at follow-up. Differences were compared using Wilcoxon signed-rank test.Results: Thirty-seven liver transplant recipients were taking the agents. Diabetes was the most common indication (n= 33) followed by obesity (n=4). Median follow up was 427 days (301,798). Among those with documented steatosis (n=21), steatosis improved in 5, worsened in 4, remained unchanged in 1, and change could not be evaluated in 11 due to lack of comparable pre and post imaging. Average weight loss was 3.2 kg (p<0.001) and BMI decreased by 1.2 kg/m2 (p<0.001). HemoglobinA1c decreased by 0.6 mmol/mol (p=0.0014), insulin requirement reduced by 7 units/day (p=0.02), and there was no change in additional antidiabetic medications.Discussion: GLP1RA and SGLT-2 inhibitors are tolerated in transplant patients and result in weight loss and better glycemic control. They are promising agents to treat recurrent or de-novo liver allograft steatosis, but further research is needed to evaluate long-term outcomes in liver transplant recipients.